Evaluation of the mechanical properties and clinical application of nickel–titanium shape memory alloy anal fistula clip - Deng, Heng; Li, Ming; Fang, Xiaoli; Zhang, Jun; Wang, Jianmin; Tang, Kun; Tang, Ran; Jia, Ru; Han, Ying; Shi, Yang; Dong, Yu'ang (Frontiers in Surgery, 2023)
Objective The study investigates the mechanical properties of a nickel–titanium shape memory alloy anal fistula clip (NiTi-AFC), studies the surgical method of treating anal fistula, and evaluates its clinical efficacy. Methods The anal fistula clip was formed in nickel–titanium alloy with a titanium content of 50.0%–51.8%. The mechanical properties and chemical properties were tested. A total of 31 patients with anal fistula were enrolled between 1 January 2020 and 1 January 2023. All patients underwent internal orifice closure surgery using NiTi-AFC, and anorectal magnetic resonance or ultrasound was performed before surgery and 6 months after surgery for diagnosis and evaluation. Fistula cure rates, length of stay, perianal pain, and Wexner incontinence scores were retrospectively compared between patients treated with NiTi-AFC and patients treated with other surgical methods. Result NiTi-AFC has a density of 6.44–6.50 g·cm−3, with a shape-restoring force of 63.8 N. The corrosion rate of NiTi-AFC in 0.05% hydrochloric acid solution at atmospheric pressure and 20°C is approximately 6.8 × 10−5 g·(m·h)−1. A total of 31 patients (male/female: 19/12, age: 43.7 ± 17.8 years) were included. Among them, 22.6% (7) had multiple anal fistula, 16.1% (5) had high anal fistula, and 48.3% (15) had perianal fistula Crohn's disease. In total, 12.9% (4/31) did not achieve primary healing, underwent fistula resection, and eventually recovered. A retrospective analysis showed that the fistula healing rate, length of stay, and anal pain of NiTi-AFC treatment were similar to those of other traditional surgeries, but the Wexner incontinence score was significantly lower. Conclusion NiTi-AFC has shape memory properties, corrosion resistance, superelastic effect, and surface cell adhesion. It is applied to internal orifice closure surgery of anal fistula, with good therapeutic effect, and can protect the anal function.